Writing beloveds : humanist Petrarchism and the politics of gender - Feng, Aileen A. (Toronto Italian studies., 2017)
"This study considers the way in which a poetic convention, the beloved to whom Renaissance amatory poetry was addessed, becomes influential political rhetoric, an instrument that both men and women used to shape and justify their claims to power. The author argues that Petrarchan poetic conventions were part of a social discourse that signaled anxiety concerning the rising place of women as intellectual interlocators, public figures, and patrons of the arts."--